Myocardial Condition Right Ventricle in Patients with Bronchial Asthma (Texas Journal of Medical Science, 2023)
The aim of the study was to assess the structural and functional state of the right ventricular myocardium in patients with moderate and severe bronchial asthma (BA) to identify early signs of impaired hemodynamics of the small circulatory circle. Materials and methods. 51 patients with moderate and severe asthma were examined during the period of exacerbation and in dynamics 12 months after the exacerbation of the disease, 10 people made up the control group. All patients were treated spirometry, bodyplethysmography, echocardiography. Results. The interrelations between the functional state of the respiratory tract, the structure of pulmonary volumes and the morphofunctional characteristics of the right ventricular myocardium in patients with asthma have been established. Conclusion. In parallel with the severity of AD, disorders of the diastolic function of the right ventricle are progressing. Changes in morphometric parameters, violations of the diastolic function of the right ventricular myocardium are associated with damage to small pathways in patients with moderate and severe bronchial asthma